2001
DOI: 10.1103/physrevlett.87.275002
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Energy Penetration in the Self-Induced Transparency Regime of Relativistic Laser-Plasma Interactions

Abstract: Two qualitatively different scenarios for the penetration of relativistically intense laser radiation into an overdense plasma, accessible by self-induced transparency, are presented. In the first one, penetration of laser energy occurs by solitonlike structures moving into the plasma. This scenario occurs at plasma densities less than approximately 1.5 times the critical one (depending on ion mass). At higher background densities, laser light penetrates only over a finite length which increases with incident … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 27 publications
11
39
0
Order By: Relevance
“…When the background plasma density n e is greater than 1.5n c , the interaction results in the generation of plasma field structure consisting of alternating plasma and vacuum regions with the CP laser penetrating into the over-dense plasmas over a finite length, which is consistent with the previous studies 23,24 . Because the formation time of the alternating plasma field structure is quite long which is about hundreds of laser period, it call for quite long incident laser pulse.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…When the background plasma density n e is greater than 1.5n c , the interaction results in the generation of plasma field structure consisting of alternating plasma and vacuum regions with the CP laser penetrating into the over-dense plasmas over a finite length, which is consistent with the previous studies 23,24 . Because the formation time of the alternating plasma field structure is quite long which is about hundreds of laser period, it call for quite long incident laser pulse.…”
supporting
confidence: 89%
“…The penetration of the ultra-short CP irradiation occurs through a soliton like behavior which is consistent with previous theoretical and fluid-Maxwell simulation studies 23,24,29 , and its propagation in the homogeneous background plasmas is quasi-static. However, it is shown that, for the ultra-short CP laser, the penetration occurs through a breaker like behavior, and there is an energy transition mechanism with a frequency 2ω 0 between the penetrated breather like structure and the background plasmas.…”
supporting
confidence: 89%
“…For the chosen parameters, the reflectivity R is nearly unity in this stage and there is no self-induced transparency. 38,39 The laser electric field E L cannot penetrate the foil and only a small number of electrons are driven out. formed.…”
Section: Multistaged Acceleration Of Thin Foilmentioning
confidence: 99%
“…Instead, there exists a transition from opacity to transparency near the laser pulse front inside a plasma. Depending on such transition process, which is actually dependent on various laser and plasma parameters, the final propagation mode of the pulse takes diverse forms: simple traveling wave modes for circular [24] and linearly [25] polarized waves, the formation of standing waves in steady states for circular [26,27] and linear polarizations [28], the formation of solitary waves [29,30], the penetration of a relativistic wave in a cavitated plasma [31,32], and the laser piston formation [33,34]. In this section, we briefly present a channel-digging process of a linearly polarized pulse along with a semi-phenomenological formula for the 1-dimensional channel-digging speed [23].…”
Section: Channel-digging Through An Overdense Plasmamentioning
confidence: 99%